Efek Emosi Negatif pada Pengobatan Penyakit Endometriosis - Helsa Nasution; M. Agung Rahmadi; Luthfiah Mawar; Ika Sandra Dewi; Milna Sari (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
This meta-analysis investigates the impact of negative emotions on the effectiveness of endometriosis treatment. Of the 1,245 articles identified, 32 studies (n=4,876 patients) met the inclusion criteria. The results revealed a significant negative correlation between negative emotions and treatment effectiveness (r = -0.38, 95% CI [-0.45, -0.31], p < 0.001). Subgroup analysis further demonstrated a stronger effect on medical treatments (r = -0.43) compared to surgical treatments (r = -0.29, p = 0.02). Additionally, negative emotions were most strongly correlated with pain intensity (r = -0.45), followed by quality of life (r = -0.39), medication adherence (r = -0.33), and patient satisfaction with treatment (r = -0.28, p = 0.02). The meta-analysis of randomized controlled trials (RCTs) (n=8) indicated that psychological interventions could significantly enhance endometriosis treatment outcomes (SMD = 0.58, 95% CI [0.39, 0.77], p < 0.001), with cognitive-behavioural therapy (CBT) being the most effective intervention (SMD = 0.67). Furthermore, the study found that the average age of patients moderates the relationship between negative emotions and endometriosis treatment (β = -0.015, p = 0.03), specifically indicating that the strongest effects of negative emotions are observed in younger patients. Finally, mediation analysis identified that pain perception, medication adherence, and maladaptive coping mechanisms are key mechanisms in the relationship between negative emotions and treatment effectiveness. These findings extend previous research by As-Sanie et al. (2014) and Lagana et al. (2017) by quantifying the impact of negative emotions and validating the effectiveness of psychological interventions as a novel contribution. The researchers advocate for a biopsychosocial approach in endometriosis management to facilitate routine screening for psychological issues and recommend the integration of holistic interventions combining medical and psychological support into standard endometriosis care.